2006
DOI: 10.1590/s0100-69162006000200019
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição longitudinal de sementes de soja e características físicas do solo no plantio direto

Abstract: As técnicas do plantio direto são complementares às atuais técnicas de conservação do solo, que envolvem menor mobilização e permanência de cobertura vegetal na superfície do solo. O trabalho foi realizado na UNESP - Jaboticabal, de novembro de 2003 a março de 2004, e teve como objetivo avaliar o efeito de culturas, manejos e marchas do trator na semeadura da soja no plantio direto. O delineamento utilizado para instalação do experimento foi em blocos ao acaso, no esquema de parcelas subsubdivididas, com quatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
13

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 5 publications
(2 reference statements)
0
7
1
13
Order By: Relevance
“…However, despite the instability of the process for this quality indicator, a minimum number of points off the lower control limit may be favorable to the operation, because it is the lowest percentage of failures that occur in the seed distribution process. Cortez et al (2006) studied the conventional mechanized sowing of soybean, through the longitudinal distribution of seeds under no-tillage system, and reported that approximately 24% had flawed spacings, results much lower when compared to the average obtained in the present work for this quality indicator. By determining the change in the seeding process (Figure 2b), through the charts of moving range, one can observe a point above the upper control limit (note nº 23) for cross-seeding in the main line (CSML), resulting from the highest and lowest variability arising between the notes n° 21 and 22 from the charts of individual values.…”
Section: Resultscontrasting
confidence: 67%
“…However, despite the instability of the process for this quality indicator, a minimum number of points off the lower control limit may be favorable to the operation, because it is the lowest percentage of failures that occur in the seed distribution process. Cortez et al (2006) studied the conventional mechanized sowing of soybean, through the longitudinal distribution of seeds under no-tillage system, and reported that approximately 24% had flawed spacings, results much lower when compared to the average obtained in the present work for this quality indicator. By determining the change in the seeding process (Figure 2b), through the charts of moving range, one can observe a point above the upper control limit (note nº 23) for cross-seeding in the main line (CSML), resulting from the highest and lowest variability arising between the notes n° 21 and 22 from the charts of individual values.…”
Section: Resultscontrasting
confidence: 67%
“…Liu et al (2004), estudando vários tipos de semeadora-adubadora conduzidos em duas diferentes velocidades de operação (7,2 e 11,3 km h -1 ) observaram que o incremento de velocidade de semeadura resultou em aumento do espaçamento médio entre plantas em todas as semeadoras testadas. Do mesmo modo, Cortez et al (2006) afirmam que a distribuição de plantas está intimamente ligada à marcha utilizada para a semeadura sendo (1) (2) que, conforme a marcha de trabalho aumenta, o espaçamento entre plantas também aumenta.…”
Section: Resultsunclassified
“…Este resultado se assemelha aos observados por Canova et al (2007) os quais verificaram que o aumento da velocidade de semeadura da cultura da soja de 6,0 para 9,0 km h -1 , interfere na distribuição de sementes e a menor velocidade proporciona distribuição de sementes mais aceitáveis. Do mesmo modo, Cortez et al (2006) observaram, trabalhando com diferentes culturas de cobertura, formas de manejo e velocidades de deslocamento na cultura da soja, que quanto maior a marcha utilizada (maior velocidade), menor a quantidade de espaçamentos aceitáveis e maior a quantidade de espaçamentos falhos. Na cultura do milho essas diferenças se tornam mais gritantes e passíveis, portanto, de representar maior influência na produtividade final uma vez que apresenta pouca plasticidade em comparação com a cultura da soja.…”
Section: Resultsunclassified
“…However, the amplitude was relatively large, ranging from 1 cm to 28 cm. This showed that plants were doubled up or missing (Cortez et al, 2006). The very small distance between plants can cause greater competition between them and reduce yield per plant and per area.…”
Section: Resultsmentioning
confidence: 99%
“…In any crop, sowing depth and seed distribution in the row should be adequate to ensure seed germination and seedling emergence and development (Martins et al, 1999;Rodrigues et al, 2016). According to Cortez et al (2006), all plant spacings from 0.5 to 1.5 times the mean spacing (MS) expected is considered acceptable. Values outside this limit are considered missing plants (more than 1.5 times the MS) or multiple plants (less than 0.5 times the MS).…”
Section: Introductionmentioning
confidence: 99%